2021
DOI: 10.1177/15579883211062681
|View full text |Cite
|
Sign up to set email alerts
|

Health and Access to Gender-Affirming Care During COVID-19: Experiences of transmasculine individuals and men assigned female sex at birth

Abstract: Since the onset of the COVID-19 pandemic, global research has suggested that the pandemic has negatively affected lesbian, gay, bisexual, transgender, and queer or questioning (LGBTQ) populations, including by limiting health care access. There is little research on the impact of COVID-19 among transmasculine persons and men assigned female sex at birth (AFAB) in the United States, who face unique health care challenges outside of the pandemic context. Between May and June of 2020, 20 transmasculine individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Communities of transgender people in other parts of the world found alternative sources of commodity supplies and service access through telehealth [ 78 ]. Telehealth also facilitated access to providers with the competency to address the physical and mental health needs of transgender populations [ 79 ]. Future studies could explore how community members negotiated these community-specific health care need challenges; and the implication of instituting practices that can enhance access to transgender community-specific services during crisis periods.…”
Section: Discussionmentioning
confidence: 99%
“…Communities of transgender people in other parts of the world found alternative sources of commodity supplies and service access through telehealth [ 78 ]. Telehealth also facilitated access to providers with the competency to address the physical and mental health needs of transgender populations [ 79 ]. Future studies could explore how community members negotiated these community-specific health care need challenges; and the implication of instituting practices that can enhance access to transgender community-specific services during crisis periods.…”
Section: Discussionmentioning
confidence: 99%
“…No divergent results in the other Central Ideas were evidenced in the discourses from this identity group of cisgender and heterosexual, trans and homosexual men, mainly in relation to establishing affective and marital relationships. In addition to that, it is important to note the fact that gay and trans men might have already been experiencing greater vulnerability before the emergence of the COVID-19 pandemic for reasons related to homophobia and transphobia, due to other experiences of intrafamily violence and to social spaces, which even favor difficulties seeking help and access to health services by LGBTQIA+ men ( Camargo et al, 2021 ; D’Angelo et al, 2021 ; Pan et al, 2021 ), requiring careful analysis to promote strategies that ensure survival, safety, and minimization of the psychosocial impacts in this population segment.…”
Section: Discussionmentioning
confidence: 99%
“…There is little research on the impact of the pandemic among trans men, but the unmet healthcare needs affected reproductive health, access to HIV PrEP (pre-exposure) care and gender-affirming procedures. 23 A systematic review concluded that mental health, health behaviours, safety and access to routine healthcare showed worse outcomes in LGBT community compared with before the pandemic or compared with heterosexual/cisgender populations. 24 The low rates of less that 20% of routine screeners in this research may be related, besides other factors described above, to the gaps in healthcare access that already existed and were intensified by Covid-19.…”
Section: Discussionmentioning
confidence: 99%